Successful rescue of antepartum eclampsia in a Chinese patient: Case report - Cao, Weiping (Medicine (Baltimore), 2019)
RATIONALE: Eclampsia is a life-threatening complication of pregnancy. Eclampsia is a leading cause of maternal and neonatal morbidity and mortality with most injury being associated with the seizures that mark the onset of the disease. It is vital that medical worker managing eclampsia have an understanding of the disease process. PATIENT CONCERNS: A 28-year-old female, G4P1, with history of caesarean section was admitted at GA34+6, in addition to headache and severe hypertension (180/120 mm Hg) and proteinuria (+++). The evaluation of coagulation parameters showed positive D-dimer and increased fibrinogen and fibrinogen degradation product (FDP) and PT percent activity. Her biochemical analysis showed a decrease in total protein and an increase in alanine transaminase (ALT) and lactate dehydrogenase (LDH) and high serum uric acid and hyperlipidemia. DIAGNOSES: She was diagnosed with severe preeclampsia (PE). INTERVENTIONS: First, the patient received magnesium sulfate therapy for convulsions control. Next, antihypertensive management of labetalol orally at a dose 100 mg and nifedipine orally at a dose 10 mg and glycerin trinitrate10 mg iv were used to maintain blood pressure in a safe range. Then, corticosteroid was given for enhancing fetal lung maturation. During preparation for cesarean section, the patient experienced suddenly seizures that lasted approximately 2 to 8 minutes. The immediate therapy is to stop the convulsions and reduce blood pressure. OUTCOMES: The patient and her baby were discharged from the hospital on the 7th day after the operation with normal blood pressure and being in a satisfactory condition. LESSONS: Eclampsia is defined as the occurrence of convulsions superimposed on the preeclampsia. The awareness of eclampsia enhances early diagnosis and timely administration of magnesium sulfate and calmative drug which are critical to avoid feto-maternal complications.